(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
There is a high level of agreement in the EU Member States with respect to a woman’s right to abortion. Poland and Malta are the only exceptions to the liberal abortion regime in Europe. Yet, this issue is still considered highly divisive. The balance between a woman’s right to abortion and the foetal right to life is still the topic of numerous legal and ethical discussions, which is a result of the recent rise of populism and anti-gender movements. In Europe, interwoven by different legal orders, international, supranational and national ones, the issue of human rights is dealt with at several levels. The EU Member States have assigned some of their sovereign rights to EU level, which is not the case with the area of reproductive rights and hence the issue of abortion is still firmly bound to state sovereignty. The first part of the paper elaborates the issue of abortion within the framework of the Convention for the Protection of Human Rights and Fundamental Freedoms (hereinafter: ECHR) and EU law. Both the ECHR and the Charter of Fundamental Rights of the European Union grant every one the right to life whereas the protection of a woman’s bodily integrity is set forth in Article 8 of the ECHR. Provisions on human rights are often featured by their general nature and it is up to judges to provide them with a more precise meaning. When it comes to international or supranational judicial bodies, such formulations might lead to controversial situations. The second part of the paper sheds light on the recent case-law of the European Court of Human Rights and the Court of Justice. Both courts have been invited to examine the current regulation of abortion in the EU Member States. Furthermore, that part of the paper explores the most relevant decisions of the above courts with respect to the conflict between the foetal on national abortion laws in the EU. This is not the first paper that deals with this issue, so the third part of the paper investigates the relevant legal literature. What is challenged is the prevalent standpoint that the level of the protection of a woman’s right to abortion is fairly low if judging by the case-law of the above courts since neither court has regarded a woman’s right to abortion as a fundamental human right. The authors try to find an answer to the question whether abortion restrictions are contrary to the fundamental principle of gender equality.